Visões da escravatura na América Latina: Sab e Úrsula - Andreta, Bárbara Loureiro (2016)
The current work aims at comparing two abolitionist novels written by women in the XIX century, one is Úrsula by the Brazilian writer Maria Firmina dos Reis and the other is Sab by the Cuban writer Gertrudis Gómez de Avellaneda. This work aims at verifying how the feminine authorship became a political place to denounce the slave regime in Brazil and in Cuba in the XIX century. Regarding the comparative literature theories and applying the intertextuality and interdisciplinary comparative presuppositions, it was carried out an analytical study about the corpus. The relevance of this research lies on rethinking the feminine authorship role in the Brazilian and Cuban literature, as well as revisiting the political, social and cultural factors that guided each one of the authors during the production of their abolitionist works. The work analysis allowed us to identify that both writers had an important role in their national literature. Both Maria Firmina dos Reis as Gertrudis Gómez de Avellaneda were women who dared to make use of the pen and ink in a time that such practice was exclusive for men. Concerning the critics about the feminine condition, in Brazil and in Cuba, both writers raised their voices and made their writing a space to denounce the injustices lived by the eighteenth-century women in their countries. However, when referring to the racial issue, it was found that the abolitionist position in Úrsula is more connected to the defense of racial equality and altruistic issues, while in Sab, through the representation of a gentle slave, it is observed that the defense of the abolition is more connected to the criollo reformism ideals.